Prognostic value of inflammatory biomarkers and GRACE score for cardiac death and acute kidney injury after acute coronary syndromes. Issue 4 (24th February 2021) - Rossi, Valentina A; Denegri, Andrea; Candreva, Alessandro; Klingenberg, Roland; Obeid, Slayman; Räber, Lorenz; Gencer, Baris; Mach, François; Nanchen, David; Rodondi, Nicolas; Heg, Dik; Windecker, Stephan; et al.
Abstract: Aims : The aim of this study was to analyse the role of inflammation and established clinical scores in predicting acute kidney injury (AKI) after acute coronary syndromes (ACS). Methods and results : In a prospective multicentre cohort including 2034 patients with ACS undergoing percutaneous coronary intervention, high-sensitivity C-reactive protein (hsCRP), neutrophil count, neutrophil-to-lymphocyte ratio (NL-ratio), and creatinine were measured at the index procedure. AKI ( n = 39, defined according to RIFLE criteria) and major cardiovascular and cerebrovascular events were adjudicated after 1 year. Associations between inflammation, AKI, and cardiac death (CD) were assessed by C -statistics and Cox proportional hazard models with log-rank test to compare survival. Patients with ACS with elevated neutrophil count >7.8 × 10 9 /L, NL-ratio >5, combined neutrophil-count/creatinine, or NL-ratio/creatinine at baseline showed a higher incidence of AKI (all P < 0.05) and CD (all P < 0.001). The risk of AKI, CD, and their combination was increased in patients with higher neutrophil count/creatinine (heart rate (HR) = 3.7, 95% cardiac index (CI) 1.9–7.1; HR = 2.7, 95% CI 1.6–4.6; HR = 3.2, 95% CI 2.1–4.9); NL-ratio/creatinine (HR = 2.1, 95% CI 1.6–4.1; HR = 2.2, 95% CI 1.3–3.8; HR = 2.3, 95% CI 1.5–3.5); and hsCRP (HR = 1.8, 95% CI 0.9–3.5; HR = 2.2, 95% CI 1.3–3.6; HR = 1.9, 95% CI 1.2–2.8) after adjustment for age, diabetes, hypertension, previous heart failure, kidney function, haemodynamic instability at admission, statin, and renin–angiotensin–aldosterone antagonists use. Subjects with higher GRACE score 1.0/NL-ratio had higher rate of AKI, CD, and both (HR = 1.4, 95% CI 0.5–4.2; HR = 2.7, 95% CI 1.3–5.9; HR = 2.1, 95% CI 1–4.3). Conclusions : Inflammation markers may predict AKI after correction for renal function at the index procedure. hsCRP performed better than the NL-ratio. However, the integration of inflammation markers to traditional risk factors or scores does not add prognostic information. Trial registration : ClinicalTrials.gov, NCT01000701. Graphical Abstract: